2020
DOI: 10.1021/acsnano.9b08667
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Switchable Nanozyme Augments Sonodynamic Therapy against Multidrug-Resistant Bacterial Infection

Abstract: Ultrasound (US)-driven sonodynamic therapy (SDT) has demonstrated wide application prospects in the eradication of deep-seated bacterial infections due to its noninvasiveness, site-confined irradiation, and high-tissue-penetrating capability. However, the ineffective accumulation of sonosensitizers at the infection site, the hypoxic microenvironment, as well as rapid depletion of oxygen during SDT greatly hamper the therapeutic efficacy of SDT. Herein, an US-switchable nanozyme system was proposed for the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
278
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(279 citation statements)
references
References 46 publications
0
278
0
1
Order By: Relevance
“…Sun et al. reported a significant decrease in the viability of cells treated with Pd@Pt‐T790 nanoplates under US irradiation, thereby indicating that hybridization of multiple materials can enhance SDT.…”
Section: Inorganic Sonosensitizersmentioning
confidence: 99%
“…Sun et al. reported a significant decrease in the viability of cells treated with Pd@Pt‐T790 nanoplates under US irradiation, thereby indicating that hybridization of multiple materials can enhance SDT.…”
Section: Inorganic Sonosensitizersmentioning
confidence: 99%
“…[ 103 ] Zheng's group prepared a Pd@Pt‐T790 nanoplatform for treating deep‐seated bacterial infections depending on nanozyme‐enhanced SDT (Figure 14B). [ 104 ] In this nanoplatform, they prepared the Pd@Pt catalase‐like nanozyme and then bridged the meso‐tetra(4‐carboxyphenyl)porphine (T790) organic sonosensitizer out of the nanozyme. Interestingly, the nanozyme activity of Pd@Pt was shown to be significantly blocked when coated with T790, and reinstated when treated with US irradiation.…”
Section: Sonodynamic Therapy Combined With Other Treatmentsmentioning
confidence: 99%
“…Reproduced with permission. [ 104 ] Copyright 2020, American Chemical Society. C) Schematic diagram for the construction of TPZ@HHSN‐C/P‐mAb and its application for combined SDT with BRT.…”
Section: Sonodynamic Therapy Combined With Other Treatmentsmentioning
confidence: 99%
“…61 Since then, it has been shown that SDT can treat solid tumours, 62-65 leukaemia 66 and atherosclerosis 67 and, moreover, remove proliferative scars and kill pathogenic microorganisms. 68,69 Since SDT was developed on the basis of PDT, some suggest that SDT shares a similar therapeutic mechanism where the ultrasonic wave triggers the sonosensitizer inside the target tissue, with production of ROS that kill the target cells. 70 Even though there is consensus in ROS production as the main cell killing mechanism, less is known about the mechanism underlying ROS production.…”
Section: Sonodynamic Therapymentioning
confidence: 99%